Developing neuroprotective strategies for treatment of HIV-associated neurocognitive dysfunction. (May 2008) - Rumbaugh, Jeffrey A; Steiner, Joseph; Sacktor, Ned; Nath, Avindra
Important advances have been made in recent years in identifying the molecular mechanisms of HIV neuropathogenesis. Defining the pathways leading to HIV dementia has created an opportunity to therapeutically target many steps in the pathogenic process. HIV itself rarely infects neurons, but significant neuronal damage is caused both by viral proteins and by inflammatory mediators produced by the host in response to infection. Highly active antiretroviral therapy (HAART) does not target these mediators of neuronal damage, and the prevalence of HIV-associated neurocognitive dysfunction has actually been rising in the post-HAART era. This review will briefly summarize our current understanding of the mechanisms of HIV-induced neurological disease, and emphasize translation of this basic research into potential clinical applications.